Working-fluid selection and performance investigation of a two-phase single-reciprocating-piston heat-conversion engine - Oyewunmi,OA; Kirmse,CJW; Haslam,AJ; Muller,EA; Markides,CN (Applied Energy, 2016)
We employ a validated first-order lumped dynamic model of the Up-THERM converter, a two-phase unsteadyheat-engine that belongs to a class of innovative devices known as thermofluidic oscillators, which containfewer moving parts than conventional engines and represent an attractive alternative for remote or off-gridpower generation as well as waste-heat recovery. We investigate the performance the Up-THERM withrespect to working-fluid selection for its prospective applications. An examination of relevant working-fluidthermodynamic properties reveals that the saturation pressure and vapour-phase density of the fluid play importantroles in determining the performance of the Up-THERM – the device delivers a higher power outputat high saturation pressures and has higher exergy efficiencies at low vapour-phase densities. Furthermore,working fluids with low critical temperatures, high critical pressures and exhibiting high values of reducedpressures and temperatures result in designs with high power outputs. For a nominal Up-THERM designcorresponding to a target application with a heat-source temperature of 360 C, water is compared withforty-five other pure working fluids. When maximizing the power output, R113 is identified as the optimalfluid, followed by i-hexane. Fluids such as siloxanes and heavier hydrocarbons are found to maximize theexergy and thermal efficiencies. The ability of the Up-THERM to convert heat over a range of heat-sourcetemperatures is also investigated, and it is found that the device can deliver in excess of 10 kW when utilizingthermal energy at temperatures above 200 C. Of all the working fluids considered here, ammonia, R245ca,R32, propene and butane feature prominently as optimal and versatile fluids delivering high power over awide range of heat-source temperatures.